JUSTE UN MOT - BYK, Christian (Journal international de bioéthique et d’éthique des sciences, 2023)
T he questions, even if they are burning questions, that current events ask us any more than the passions aroused by situations felt to be unjust can completely guide our analysis and our questions on how to act to remedy them. At the time when we invited our Russian colleagues to prepare this issue, Russia’s second war against Ukraine had not yet begun with its extreme humanitarian – or rather “inhumanitarian” – consequences for the invaded and martyred country. in its population as in its national identity. The consequences, still difficult to measure, of this invasion desired by the Russian power as a major political project aimed at replacing the country in "its historical trajectory", are now measured at the international level in political, economic and cultural dimensions, including sanctions against Russia. Should the immediate time then shake up a work which, because it is academic, would be at odds with the present situation? Should we appropriately postpone the publication of academic works, which take place over a longer period of time, which B. Lichertman, the guest editor-in-chief of this issue, places in continuity with a previous issue published in 2005. We chose to think, on the contrary, that these texts, diverse in terms of what they say and the way in which they say it, were a testimony, through the prism of questions concerning medical ethics, of what Russia is today and that they thus provided a useful perspective to better analyze Russian society. It is true that the philosophy of bioethics, which I make my own, is to consider it as a phenomenon revealing the social transformations of a society. This is also what I expressed in 1994 to Yvan Frolov, the first president of the National Bioethics Commission of Russia and Gorbachev’s promoter of Perestroika. And now let the reader be the judge!